Chitosan-coated titanium screws: Enhancing biofilm resistance, mechanical stability, and osseointegration in orthopedic implants - Niranjan Ghimire; Manish Rayamajhi; Yuyu Sun; Ying Deng (Journal of Applied Biomaterials & Functional Materials)
Orthopedic implant-associated infections, primarily caused by biofilm-forming Staphylococcus aureus , pose significant clinical challenges. These infections often lead to implant failure, prolonged antibiotic treatments, and an increased risk of revision surgeries, emphasizing the need for effective biofilm-resistant implant materials. In this study, we present a dual-functional titanium screw (Ti-S) grafted with chitosan (Cs), a biocompatible polymer known for its osteogenic and antimicrobial properties while maintaining mechanical integrity. The chitosan-modified titanium screw (Cs-Ti-S) was prepared via chemical immobilization to enhance resistance to biofilm formation while promoting osseointegration and preserving biomechanical integrity. Biomechanical testing confirmed that chitosan modification did not compromise mechanical performance, as Cs-Ti-S exhibited a torsional yield strength of 1.70 ± 0.00 Nm compared to 1.76 ± 0.05 Nm for unmodified titanium screws (Un-Ti-S), and an axial pullout force of 68.66 ± 14.36 N for Cs-Ti-S versus 70.33 ± 9.71 N for Un-Ti-S. Micro-scratch tests revealed similar hardness values (1.26 ± 0.03 GPa for Cs-Ti-S vs. 1.40 ± 0.07 GPa for Un-Ti-S) and scratch resistance, ensuring surface durability. Gene expression analysis showed upregulated β1-integrin on Cs-Ti-S at 24 h post-infection, indicating improved osteoblast adhesion. Scanning electron microscopy (SEM) analysis confirmed significantly reduced bacterial biofilm formation on Cs-Ti-S. Moreover, the combination of povidone-iodide (PI) treatment on Cs-Ti-S surfaces significantly inhibited biofilm formation over 7 days, unlike Un-Ti-S, which retained significant adhesion. These results suggest chitosan grafting as a scalable, non-antibiotic strategy to enhance antimicrobial resistance and osseointegration.